The Effect of an IoT-based Microcontroller Training Kit on Psychomotor Learning Outcomes in Microcontroller and Microprocessor Programming - Habibi, Mohammad Wildan; Buditjahjanto, I Gusti Putu Asto; Rijanto, Tri; Anifah, Lilik; Abdillah, Rifqi; Al Rosyid, Harun; Hakiki, Muhammad; Wibawa, Ramadhan Cakra; Husnaini, Siti Jamiatul (E3S web of conferences, 2025)
This study analyzed the impact of an Internet of Things (IoT)- based microcontroller training kit on the psychomotor learning outcomes of vocational students learning microcontroller and microprocessor programming. Two classes were used in this study as samples, where the experimental class used an IoT-based training kit while the control class used a general microcontroller training kit. The assessment instrument was developed referring to Dave’s psychomotor taxonomy theory and was evaluated using validity and reliability tests (Cronbach’s Alpha > 0.87). The results of ANOVA showed that there were significant differences between the two groups (p = 0.000 < 0.05), and the mean psychomotor score of the experimental class (87) was higher than that of the control class (81). IoT learning media have been proven to not only improve psychomotor skills but also provide contextual and relevant learning experiences with the demands of industry 4.0. Thus, the use of IoT-based training kits is recommended as an innovative learning medium in vocational schools, especially in developing students’ applied skills directly and measurably.